2014
DOI: 10.1073/pnas.1321155111
|View full text |Cite
|
Sign up to set email alerts
|

H-Ras forms dimers on membrane surfaces via a protein–protein interface

Abstract: The lipid-anchored small GTPase Ras is an important signaling node in mammalian cells. A number of observations suggest that Ras is laterally organized within the cell membrane, and this may play a regulatory role in its activation. Lipid anchors composed of palmitoyl and farnesyl moieties in H-, N-, and K-Ras are widely suspected to be responsible for guiding protein organization in membranes. Here, we report that H-Ras forms a dimer on membrane surfaces through a protein-protein binding interface. A Y64A poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
166
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(171 citation statements)
references
References 62 publications
5
166
0
Order By: Relevance
“…It is well established that numerous GTPases are regulated by dimerization [24,[39][40]. Also our previous experiments revealed that DiRas3 is able to heterodimerize with active H-Ras [27].…”
Section: Diras3 Enhances the Side-to-side Homodimerization Of Ksr1mentioning
confidence: 85%
“…It is well established that numerous GTPases are regulated by dimerization [24,[39][40]. Also our previous experiments revealed that DiRas3 is able to heterodimerize with active H-Ras [27].…”
Section: Diras3 Enhances the Side-to-side Homodimerization Of Ksr1mentioning
confidence: 85%
“…Computer simulations suggest that lipid anchors in the HVR of H-Ras and N-Ras are capable of forming dimers and nanoclusters. 71,73,83 In-cell studies of the K-Ras lipid anchor using Homo-FRET and electron microscopy also demonstrate that the lipid anchor is sufficient for dimerization and clustering on the membrane. 84 How can the HVR, -that is not involved in nucleotide binding or hydrolysis -affect dimer and nanocluster formation in a nucleotide dependent manner?…”
Section: Ras Dimerization Oligomerization and Clusteringmentioning
confidence: 96%
“…H-Ras dimerization in lipid bilayers has been demonstrated by time-resolved fluorescence spectroscopy and microscopy, however no higher order oligomers of H-Ras were observed. 73 Variations in membrane composition had no effect on H-Ras dimerization. N-Ras also dimerizes in the GDP-bound inactive state in POPC (1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine) bilayers.…”
Section: Ras Dimerization Oligomerization and Clusteringmentioning
confidence: 98%
“…5). An allosteric level of control over dimerization could be an important regulator of Ras interactions with other signaling proteins (63), begging the question of whether the dimers of each isoform should be treated as discrete entities with overlapping yet unique functional and structural characteristics.…”
Section: A Structural View Of the Allosteric Lobementioning
confidence: 99%